New Normal and Social Change in Indonesia Society - Putu Nadia Aurelia Tasya (Universitas Pendidikan Ganesha, 2021)
The world is currently experiencing a disastrous disease outbreak that is very disturbing to humans, namely the Coronavirus outbreak. This virus originates and originates from the city of Wuhan, China. Another name for Coronavirus is the Covid-19 outbreak. Indonesia is one of the countries in the world affected by this virus until it has entered a pandemic status. The Indonesian government and the people have tried their best to fight this pandemic and many policies have been issued regarding health protocols to protect the nation from this very fast-spreading disease outbreak. One of the policies issued is the new normal, which is a situation where all community activities can be carried out as usual but are still required to comply with existing regulations. For examples, wearing a mask, staying away from the crowd, and washing your hands cleanly. It cannot be denied that this policy can bring about social changes or changes in habits in society towards a society that is responsive to health, hygienic, and cares for the environment.